2017
DOI: 10.1186/s13013-017-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

Upright, prone, and supine spinal morphology and alignment in adolescent idiopathic scoliosis

Abstract: BackgroundPatients with adolescent idiopathic scoliosis (AIS) are usually investigated by serial imaging studies during the course of treatment, some imaging involves ionizing radiation, and the radiation doses are cumulative. Few studies have addressed the correlation of spinal deformity captured by these different imaging modalities, for which patient positioning are different. To the best of our knowledge, this is the first study to compare the coronal, axial, and sagittal morphology of the scoliotic spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 25 publications
1
62
0
Order By: Relevance
“…Despite inherent design weaknesses that are mostly related to the difficulty for in vitro studies to precisely replicate the biomechanical effects of decompression and instrumentation in patients with scoliotic spines, it has to be noted that all radiographic images of the specimens were taken in a supine position rather than a more natural weight-bearing standing position, which is known to increase Cobb angle measurements in patients with scoliosis and might explain why we did not find any lateral slippage. 10,51 Also, during mechanical testing, we did not apply compressive axial loading. However, applying axial compression while testing would create additional moments, especially in spines with various degrees of scoliosis, that could interfere with the loading directions and consequently have an effect on the loaddisplacement data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite inherent design weaknesses that are mostly related to the difficulty for in vitro studies to precisely replicate the biomechanical effects of decompression and instrumentation in patients with scoliotic spines, it has to be noted that all radiographic images of the specimens were taken in a supine position rather than a more natural weight-bearing standing position, which is known to increase Cobb angle measurements in patients with scoliosis and might explain why we did not find any lateral slippage. 10,51 Also, during mechanical testing, we did not apply compressive axial loading. However, applying axial compression while testing would create additional moments, especially in spines with various degrees of scoliosis, that could interfere with the loading directions and consequently have an effect on the loaddisplacement data.…”
Section: Discussionmentioning
confidence: 99%
“…In this study they found a generalized underestimation of morphological parameters of the scoliotic deformity in the supine and prone positions as compared with the standing position, although a significant correlation of thoracic and lumbar Cobb angles/apical vertebral rotation was still evident among different body positions by different imaging modalities. 21 All these studies agreed that Cobb angles are markedly underestimated by a margin difference of 2 to 21 degrees (mean: 8.8 degrees) between the supine and erect positions (►Table 1). Further, not only do these studies show an underestimation of the Cobb angle between standing and supine/ prone positions in scoliosis assessment, but also in vertebral rotation, thoracic kyphosis, and lumbar lordosis measurements.…”
Section: Effects Of Gravity On Spinal Curvesmentioning
confidence: 53%
“…(20,21) The diagnosis and management decision of scoliosis relies on the Cobb angle measurement and thus these measurements must be accurate and consistent. The measurement error for human subjects has already been exempli ed from various aspects (5,8,(22)(23)(24). However the effects of mouse positioning on angle measurement is unclear.…”
Section: Discussionmentioning
confidence: 99%